The existential function of right‐wing authoritarianism1. Issue 5 (4th February 2019) - Womick, Jake; Ward, Sarah J.; Heintzelman, Samantha J.; Woody, Brendon; King, Laura A.
Abstract: Objective: Four studies tested the existential and existential buffering functions of right‐wing authoritarianism (RWA). We tested whether the facets of meaning mediated these functions. Method: All studies measured RWA and meaning in life (MIL). Study 1, N = 2, 319, also measured covariates, including Protestant Work Ethic and religiosity. Study 2, N = 505, examined RWA and meaning facets (purpose, coherence, and significance), and measured religiosity. Study 3, N = 971, measured psychological distress to test the existential buffering function of RWA. Study 4, N = 833, tested this hypothesis using meaning facets and tested for moderated mediation. Results: In all studies, RWA and MIL were positively correlated. In Study 1, Protestant Work Ethic and religiosity weakened this association. In Study 2, significance mediated the association between RWA and global MIL. Religiosity wiped out the relationship between RWA and meaning variables, except significance. Study 3 supported the existential buffering hypothesis: distress and global MIL were less strongly related among those high on RWA. Study 4 replicated this finding for MIL facets. Significance mediated the existential buffering function of RWA. Conclusions: Findings extend scientific knowledge by demonstrating that RWA contributes to MIL, particularly existential mattering, and especially for those experiencing distress. We discuss implications for our understanding of RWA and MIL.